Pengembangan Media Pembelajaran Interaktif Spinning Wheel Game Berbantuan Power Point Pada Mata Pelajaran Sejarah Kelas XII IPS SMAN 19 Tebo - Devi Nur Prawesti; Liza Husnita; Meldawati Meldawati (Journal on Education, 2023)
This article aims to describe the development of an interactive learning Spinning Wheel Game, assisted by Power Point, and to test the validity and feasibility of the Spinning Wheel Game media assisted by Power Point. This study uses research and development methods (Research and Development). With the 4D model, it has four stages: Define, Design, Develop, and Disseminate. The following are the results of the study: First, the validity test by an expert in a very valid category obtained a percentage of 84.37% from various aspects of the assessment. Aspects of feasibility include the material percentage of 85%, the feasibility aspect of the language percentage of 75%, and the feasibility aspect of the media percentage of 95%. Second, the practicality test by the teacher, with a percentage level of 85.41%, is "very practical". A Student response questionnaire totaling 28 students obtained a percentage of 84.01% with the title "very practical". The conclusion of this research is that the development of learning media at the definition (Planning) stage is carried out by analyzing students, analyzing curriculum, and analyzing material. In the Develop stage, media selection, format selection, material preparation, and instrument design were carried out, these steps, the development of an interactive Spinning Wheel Game for assisted learning was obtained from Power Point.